2020
DOI: 10.36590/jika.v2i1.38
|View full text |Cite
|
Sign up to set email alerts
|

Regional Language Mini Poster as an Alternative Media for Health Promotion Hand Hygiene

Abstract: Angka kejadian diare di Desa Sejahtera mengalami trend peningkatan dari tahun ke tahun. Salah satu upaya pencegahan penyakit diare adalah mencuci tangan pakai sabun dan air mengalir setelah buang air besar, sebelum menyiapkan makanan, dan sebelum makan. Penelitian bertujuan mengetahui efektivitas mini poster berbahasa daerah terhadap kepatuhan ibu mencuci tangan di Desa Sejahtera. Penelitian ini menggunakan desain eksperimen semu (quasy experiment) non-equivalent control group. Sampel penelitian sebanyak 30 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…In addition, a media should use daily language to make it easier for readers to understand. 24 , 26 The language used in this infographic was considered satisfying because it used brief, concise, simple sentences in accordance with the Indonesian Improved Spelling ( Ejaan Yang Disempurnakan /EYD). To comprehend messages in a media is closely related to the way the message is conveyed, whether the message is complete or not, also the usage of images in the media.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a media should use daily language to make it easier for readers to understand. 24 , 26 The language used in this infographic was considered satisfying because it used brief, concise, simple sentences in accordance with the Indonesian Improved Spelling ( Ejaan Yang Disempurnakan /EYD). To comprehend messages in a media is closely related to the way the message is conveyed, whether the message is complete or not, also the usage of images in the media.…”
Section: Discussionmentioning
confidence: 99%
“…Wiji & Fitri (2020) using posters as a media strategy for nutrition education to increase knowledge of postpartum mothers, babies, and toddlers. Another research was conducted by Andriani, Suwarni, & Arfan (2020) by using posters as an alternative media to wash hands. Wiji & Fitri (2020) and Andriani et al (2020) have something in common with this study, namely using poster media as a health promotion medium.…”
Section: Discussionmentioning
confidence: 99%
“…Another research was conducted by Andriani, Suwarni, & Arfan (2020) by using posters as an alternative media to wash hands. Wiji & Fitri (2020) and Andriani et al (2020) have something in common with this study, namely using poster media as a health promotion medium. The results also showed that posters were suitable for use as a health promotion medium.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini dilakukan untuk pengingat agar para santri dan pengelola santri serta tamu yang ada di Ponpes tersebut agar selalu dapat menerapkan protokol kesehatan. Poster efektif untuk menimbulkan kesadaran seseorang sehingga berpengaruh pada perilakunya (Zhu, et al, 2017) (Barik, Purwaningtyas, & Astuti, 2019) (Andriani, Suwarni, & Arfan, 2020).…”
Section: Simpulanunclassified